Phase II study of bortezomib, cyclophosphamide and dexamethasone as induction therapy in multiple myeloma: DSMM XI trial. (29th September 2017) - Einsele, Hermann; Engelhardt, Monika; Tapprich, Christoph; Müller, Jürgen; Liebisch, Peter; Langer, Christian; Kropff, Martin; Mügge, Lars O.; Jung, Wolfram; Wolf, Hans‐Heinrich; Metzner, Bernd; Hart, Christina; et al.
Summary: We assessed the safety and efficacy of bortezomib, cyclophosphamide and dexamethasone (VCD) induction therapy in previously untreated multiple myeloma patients. A total of 414 patients received three 21‐day cycles of VCD prior to autologous stem‐cell transplantation (ASCT). Most common grade ≥3 adverse events were leucopenia (31·4%) and thrombocytopenia (6·8%). The overall response rate (ORR) by investigator‐based assessment was 85·4%. Most patients (74%) underwent successful central laboratory‐based molecular cytogenetic analysis. No clinically relevant differences in ORR post‐induction were seen between patients with or without high‐risk cytogenetic abnormalities (86·2% vs. 84·3%). Further follow‐up data are available for 113 patients receiving ASCT who were included in a prospective consolidation trial (median follow‐up, 55·5 months); median progression‐free survival (PFS) was 35·3 months and median overall survival (OS) was not reached. In patients with high‐risk versus standard‐risk cytogenetics, median PFS was 19·9 vs. 43·6 months ( P <  0·0001), and median OS was 54·7 months versus not reached ( P  = 0·0022). VCD is an effective and tolerable induction regimen; results suggest that VCD induces high response rates independently of cytogenetic risk status, but after long‐term follow‐up, cytogenetic high risk is associated with markedly reduced PFS and OS post‐ASCT.